2012
DOI: 10.1042/bj20111020
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor-C (PDGF-C) activation by serine proteases: implications for breast cancer progression

Abstract: The PDGF family members are potent mitogens for cells of mesenchymal origin and serve as important regulators of cell migration, survival, apoptosis, and transformation. Tumor-derived PDGF ligands are thought to function in both autocrine and paracrine manners, activating receptors on tumor and surrounding stromal cells. PDGF-C and -D are secreted as latent dimers, unlike PDGF-A and -B. Cleavage of the CUB domain from the PDGF-C and -D dimers is required for their biological activity. At present, little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
3
34
1
Order By: Relevance
“…Hence, PDGF-induced cell proliferation could very well sustain a desmoplastic reaction while supporting tumor progression, thus fueling a protumorigenic vicious cycle (20). Some studies suggest that PDGF could sustain or even initiate desmoplasia in breast cancer (148,326), while others point to the fact that PDGF is a promigratory factor (67) as well as an EMT regulator (388). Furthermore, PDGF expression can also affect other growth factors, as inhibition of stromal PDGF receptors in a murine model of cervical cancer was shown to alter the levels of expression of the fibroblast growth factors (FGF)-2 and -7 (287).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…Hence, PDGF-induced cell proliferation could very well sustain a desmoplastic reaction while supporting tumor progression, thus fueling a protumorigenic vicious cycle (20). Some studies suggest that PDGF could sustain or even initiate desmoplasia in breast cancer (148,326), while others point to the fact that PDGF is a promigratory factor (67) as well as an EMT regulator (388). Furthermore, PDGF expression can also affect other growth factors, as inhibition of stromal PDGF receptors in a murine model of cervical cancer was shown to alter the levels of expression of the fibroblast growth factors (FGF)-2 and -7 (287).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…While the PDGF ligands A and B are secreted as active heterodimers or homodimers, PDGF ligands C and D are secreted as latent homodimers that require proteolytic activation (Li et al 2000;Bergsten et al 2001). tPA, uPA, and matriptase have been shown to proteolytically activate PDGF-C and PDGF-D (Hurst et al 2012). Pericellular activation of HGF is mediated by the serine proteases matriptase and hepsin (Owen et al 2010).…”
Section: Proliferation and Survivalmentioning
confidence: 99%
“…In colorectal tumors, PDGF-C overexpression is significantly associated with worse overall and relapse-free survival [31]. The enforced expression of PDGF-C has also been shown to promote the growth of breast cancer cells [34]. In this study, we demonstrated that PDGF-C promotes the growth of fibrosarcoma cells and ES cells.…”
Section: Pdgf-c Is Required For Anchorage-dependent and -Independent mentioning
confidence: 51%